DEHUMANISASI PEREMPUAN DI ERA DIGITAL 4.0 : SEBUAH ANALISIS TERHADAP AKUN INSTAGRAM @project_model_e.x.o, @maxi_lex92, DAN @lecalecxis - ADITA MIRANTI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This paper aims to examine more deeply the symptoms of dehumanization that occur in women in the digital age. Through social media, women are often represented and represent themselves as objects. One of them on Instagram is manifested through the body. On Instagram women often display their existence by reconstructing body shapes. This is done not infrequently as an effort to seek recognition of femininity in cyberspace. Dehumanization of women in social media occurs through what is represented and the way women represent themselves through social media. This research is a case study, which specifically looks at problems with an interpretive qualitative approach. The diagram above is a research subject that will be analyzed by confirming with the informant, through virtual interviews. Furthermore, the data is ’dialogue’ with the relevant theoretical framework. The results show that there is a condition where women are attracted to high permissive areas. The argument is the need for digital self-existence which is seen as more important than truth, aesthetics and ethics. Women, in this case, are the subjects of silence who are subject to the modification of all things, which finally unwittingly drags them strongly into dehumanization.